Konsekuensi Hukum Tidak Adanya Perjanjian Perkawinan Terhadap Harta Kekayaan dalam Perkawinan Menurut KUHPerdata : Penerapan Sistem Persatuan Harta Secara Default - Aina Mulia Rizky; Parlaungan Gabriel Siahaan; na Diva Ivan De La Pena Ginting; Desi Marlina Sidabutar; Nazwa Clarissa; Sinta Uli Nainggolan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study discusses the legal consequences of the absence of a marriage agreement on marital property according to the Indonesian legal system, especially based on the Civil Code and the Marriage Law No. 1 of 1974. By default, the absence of a marriage agreement leads to the enactment of a system of property union, in which all property acquired during the marriage is considered joint property. This condition has various legal implications, such as the vulnerability of personal property to third-party claims, difficulties in proving ownership of inherited property, and potential conflicts in the division of property in the event of divorce or death of one of the spouses. This study also highlights the difference in the regulation in Islamic law that does not recognize the automatic union of property, but still has the potential to cause disputes if there is no written agreement. The research method used is empirical normative with a qualitative approach, examining positive legal provisions and practices that develop in society. The results of the study show that low public understanding and negative stigma towards marriage agreements are the main factors in the low making of these agreements. The Constitutional Court Decision No. 69/PUU-XIII/2015 which allows the making of agreements during the marriage period expands legal protection, but its implementation still faces challenges. This study recommends the need to increase legal education and socialization on the importance of marriage agreements to provide certainty and fair legal protection for the parties in the institution of marriage.